“The most modern dining hall in the city”: Chinese Immigrants, Restaurants, and Social Spaces in St. John’s, Newfoundland, 1918–1945 - Wright, Miriam (Acadiensis, 2021)
The article looks at Chinese immigrants in Newfoundland, focusing on the restaurants they opened in St. John’s from 1918 through the mid-1940s. For the Chinese immigrants, restaurants were paths to economic stability and, for some, a way to establish themselves as respected members of the community. The restaurants were, however, also contested spaces, as civil authorities, drawing on racial, gendered, and class-based assumptions, saw them – and the social interactions taking place within them – as threatening to the moral order. This history of Chinese immigrants and their restaurants offers a diverse and complex urban history of St. John’s.